Staphylococcus aureus and methicillin-resistant Staphylococcus aureus in juvenile green turtle (Chelonia mydas) carcasses, rearing seawater, feed and their antibiotic resistances - Thanaporn Chuen-im; Korapan Sawetsuwannakun; Thongchai Taechowisan; Nakarin Kitkumthorn (PeerJ)
Staphylococcus aureus is an opportunistic bacterium that can infect humans and animals. We previously reported that Staphylococcus aureus as one of the most frequent Gram-positive bacteria found in the infection in juvenile green turtles (Chelonia mydas) from the Sea Turtle Conservation Center of Thailand (STCCT), Sattahip, Chonburi Province. It was also the most detected Gram-positive bacteria in rearing seawater. In this study, we investigated the presence of S. aureus in coastal seawater used as supply water to rearing containers, rearing water, fish fillet used as feed, and juvenile green turtle carcasses at STCCT. From the results, S. aureus can be isolated from rearing water, fish fillet, and juvenile turtle carcasses but not from incoming coastal seawater. The determination of antibiotic resistance against 11 drugs demonstrated that more S. aureus from juvenile turtles were antibiotic resistant than the isolates from rearing water and fish fillet. Furthermore, a higher isolate number of methicillin-resistant S. aureus (MRSA) was found in juvenile turtle carcasses. We also detected penicillin-susceptible MRSA and mecA-positive methicillin-susceptible S. aureus from juvenile turtles and fish fillet, respectively. Differences in the antibiotic resistance profiles were observed in this study compared with our previous observation. A change in the antibiotic resistance properties possibly continued in S. aureus. This finding suggests that the status of animal health is at high risk and emphasizes the need for a surveillance plan and treatment strategies to confront this serious threat.